Dissecting the genetic architecture of glucosinolate compounds for quality improvement in flowering stalk tissues of Brassica napus - Changbin Gao; Fugui Zhang; Yang Hu; Liping Song; Liguang Tang; Xueli Zhang; Cong'an He; Aihua Wang; Xiaoming Wu (Horticultural Plant Journal, 2023)
Glucosinolates (GSLs) and their hydrolytic products contribute to the quality traits of rapeseed flowering stalk tissues, such as taste, flavor and anticarcinogenic properties (Glucoraphanin). However, little is known about the genetic mechanisms of GSL accumulation in rapeseed flowering stalks. In this study, the variation and genetic architecture of GSL metabolites in flowering stalk tissues were investigated for the first time among a panel of 107 accessions. All GSL compounds exhibited continuous and wide variations in the present population. Progoitrin, glucobrassicanapin and gluconapin were the most abundant GSL compounds. Five quantitative trait loci (QTL) significantly associated with three GSL compounds were identified by genome-wide association study. GRA_C04 was under selected during modern breeding, in which the ratio of lower GSL haplotype (HAP2) in the accessions bred before 1990 (52.56%) was significantly lower than that after 1990 (78.95%). Four candidate genes, BnaA01. SOT16, BnaA06. SOT17, BnaA06. MYB51a, and BnaA06. MYB51b, were identified in the GTL_A01 and 4OH_A06 regions. These findings provide new insights into GSL biosynthesis in flowering stalk tissues and facilitate quality improvement in rapeseed flowering stalks.